Bones are forever - Reichs, Kathy (New York : Scribner, 2012)
Forensic anthropologist Tempe Brennan examines the bodies of three babies while Detective Ryan investigates their mother in a case with ties to the high-stakes world of diamond mining.
Keywords: Brennan, Temperance (Fictitious character) -- Fiction; Women forensic anthropologists -- Fiction; Forensic anthropologists -- Fiction; Infanticide -- Canada -- Fiction; Diamond mines and mining -- Canada -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction